Bacterial Toxin and Effector Regulation of Intestinal Immune Signaling - Woida, Patrick J.; Satchell, Karla J. F. (Frontiers in Cell and Developmental Biology, 2022)
The host immune response is highly effective to detect and clear infecting bacterial pathogens. Given the elaborate surveillance systems of the host, it is evident that in order to productively infect a host, the bacteria often coordinate virulence factors to fine-tune the host response during infection. These coordinated events can include either suppressing or activating the signaling pathways that control the immune response and thereby promote bacterial colonization and infection. This review will cover the surveillance and signaling systems for detection of bacteria in the intestine and a sample of the toxins and effectors that have been characterized that cirumvent these signaling pathways. These factors that promote infection and disease progression have also been redirected as tools or therapeutics. Thus, these toxins are enemies deployed to enhance infection, but can also be redeployed as allies to enable research and protect against infection.